Association between Mycoplasma and Ureaplasma airway positivity, ammonia levels, and outcomes post–lung transplantation: A prospective surveillance study. Issue 6 (10th December 2020) - Buzo, Bruno F.; Preiksaitis, Jutta K.; Halloran, Kieran; Nagendran, Jayan; Townsend, Derek R.; Zelyas, Nathan; Sligl, Wendy I.
Abstract: Hyperammonemia syndrome (HS) is a rare complication with high mortality described after lung transplantation. Its pathophysiology is still unclear, but previous studies, including murine models, have linked the identification of Mycoplasmataceae in airway specimens with HS occurrence. This study explores the association between Mycoplasmataceae polymerase chain reaction (PCR) positivity, ammonia levels, HS, and mortality post–lung transplant. Adults who underwent lung transplantation between July 2017 and August 2019 had prospective surveillance testing for Mycoplasma and Ureaplasma using PCR on post‐operative bronchoscopy samples. One hundred and fifty‐nine patients underwent lung transplantation during the study period. Mean age was 54 (±13) years; baseline diseases were predominantly pulmonary fibrosis (37.7%) and chronic obstructive pulmonary disease (35.8%). Mycoplasma and/or Ureaplasma airway positivity was found in 42 (26.4%) of tested patients, represented mostly by M . salivarium (26/43; 60.4%), U . parvum (7/43; 16.2%), and U . urealyticum (5/43; 11.6%). Median peak ammonia levels were higher in those with Ureaplasma colonization compared to uncolonized patients ( p  = .04), however, only three patients developed HS. Recipient airway Ureaplasma positivity was independently associated with younger (aOR 0.94, 95% CI 0.88–0.99, p  = .04) and female donors (aOR 4.29; 95% CI 1.01–18.2, p  = .05). Abstract : Ureaplasma spp. identification in bronchoalveolar lavage is associated with young female donors and may correlate with elevated serum ammonia levels and increased risk of hyperammonemia syndrome in lung transplant recipients.